Improved Optoelectronic Characteristics of Post-Annealed Ti/Al/ITO Transparent Conducting Electrodes Deposited on n-GaN - Ali, Ahmad Hadi; Shuhaimi, Ahmad; Hassan, Zainuriah (2015)
We report on the improved structural. electrical and optical properties of the Ti/AI/ITO transparent conducting electrodes (TCEs) deposited on n-GaN. The TCEs were deposited by RF/DC magnetron sputtering under Ar ambient at room temperature. The as-deposited TCEs were annealed at 600 oc in N2 ambient for 15 min. The structural, electrical and optical properties of the TCEs were characterized by 2-Theta X-ray diffraction (XRD), atomic force microscope (AFM). Hall effects, 1-V and UV-visible measurement system. From XRD measurement, significant ITO (222) and (411) peaks were observed after the sample was post-annealed at 600 oc. Morphological analysis by AFM shows that surface roughness Rq of the post-annealed sample is smoother as compared to the as-deposited sample. The electrical resistivity of the TCEs layer decreases to 8.607x10-5n-cm after the post-annealing process. Further analysis on the 1-V characteristics reveals that the post-annealed samples have better Ohmicbehavior than the as-deposited sample. The post-annealed sample shows high optical transmittance characteristics in visible spectrum of -95%. The figure of merit (FOM) of the as deposited and post-annealed samples are 2.39x1 0-40-1 and 5.91 x1 o-2Q-1, respectively. Therefore, the post-annealed TCEs show the best electrical and optical quality due to the improved structural and morphological characteristics.